Failure to identify modifiers of NEBULIN-related nemaline myopathy in two pre-clinical models of the disease - Qiu, Boyang (Biol Open, 2019)
Nemaline myopathy is a rare neuromuscular disorder that affects 1 in 50,000 live births, with prevalence as high as 1 in 20,000 in certain populations. 13 genes have been linked to nemaline myopathy (NM), all of which are associated with the thin filament of the muscle sarcomere. Of the 13 associated genes, mutations in NEBULIN (NEB) accounts for up to 50% of all cases. Currently, the disease is incompletely understood and there are no available therapeutics for patients. To address this urgent need for effective treatments for patients affected by NM, we conducted a large scale chemical screen in a zebrafish model of NEB-related NM and an N-ethyl-N-nitrosourea (ENU)-based genetic screen in a mouse model of NEB exon 55 deletion, the most common NEB mutation in NM patients. Neither screen was able to identify a candidate for therapy development, highlighting the need to transition from conventional chemical therapeutics to gene-based therapies for the treatment of NM.